2010
DOI: 10.1089/pho.2009.2591
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy in Planktonic and Biofilm Cultures of Aggregatibacter actinomycetemcomitans

Abstract: Photodynamic therapy-generated ROS inactivates A. actinomycetemcomitans both in planktonic and biofilm cultures, even in small concentrations of the photosensitizing agent, and it does not cause damage to fibroblast cells under the same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 32 publications
3
41
0
5
Order By: Relevance
“…1A). This is in agreement with previously published reports using blue light (400-500 nm) to photoactivate RB [10,12]. Also, light irradiation alone (240 s) had no effect on E. faecalis but reduced F. nucleatum viability by approximately 10%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1A). This is in agreement with previously published reports using blue light (400-500 nm) to photoactivate RB [10,12]. Also, light irradiation alone (240 s) had no effect on E. faecalis but reduced F. nucleatum viability by approximately 10%.…”
Section: Discussionsupporting
confidence: 93%
“…The use of blue light-mediated aPDT has stemmed from the widespread availability of dental blue-light sources having a broad emission spectrum (400-500 nm) and a high energy per photon [11]. Blue light-activated rose bengal was shown to inactivate S. mutans, A. actinomycetemcomitans and C. albicans in several research reports that also confirmed the influence of the amount of light energy delivered on bacterial killing [10,12,13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, for both the continuous and intermittent groups, increasing concentrations of eosin Y did not improve antibacterial activity as observed for the 40-80 M concentrations. As reported by Goulard et al, when high concentrations of photosensitizers are incubated for longer periods of time, they can form aggregates, thereby decreasing treatment efficiency [32]. Also, a longer irradiation time may have accelerated photobleaching of the photosensitizer, which was shown to occur with irradiation times longer than 15 min [33].…”
Section: Discussionmentioning
confidence: 89%
“…The antibacterial properties of Photosan light-activated with a commercially available dental photopolymerizer emitting blue light were reported against the Gram-positive S. mutans and Enterococcus faecalis in planktonic cultures [6]. Other research indicates that Aggregatibacter actinomycetemcomitans, a Gram-negative pathogen causing periodontal disease, can be inactivated by rose bengal exposed to bluelight irradiation, both in planktonic and biofilm cultures [7]. Papastamou et al assessed various formulations of ruthenium exposed to blue light for inactivating Fusobacterium nucleatum and Porphyromonas gingivalis and reported a significant reduction in viability of both pathogens after treatment [8].…”
Section: Introductionmentioning
confidence: 99%